Sedentary Behavior and Lack of Physical Activity among Children in Indonesia - Laily Hanifah; Nanang Nasrulloh; Dian Luthfiana Sufyan (MDPI AG, 2023)
Sedentary behavior and lack of physical activity among children in Indonesia is an important issue that needs to be addressed. It is estimated that 57% of children in Indonesia have insufficient physical activity. Studies have shown that children who engage in sedentary behaviors are at an increased risk for various negative health outcomes, including obesity, type 2 diabetes, cardiovascular disease, and poor mental health, compared to physically active ones. This article aims to provide recommendations to increase physical activity and reduce passive behavior in children in Indonesia. This is a commentary article developed from observing the recent progress of sedentary behavior and lack of physical activity among children in Indonesia and the potential consequences. The level of inactive behavior in children in Indonesia is relatively high. Factors that contribute to sedentary behavior and lack of physical activity among children in Indonesia are the increasing use of electronic devices and screen time, the lack of safe and accessible places to be physically active, the COVID-19 pandemic, as well as cultural and social norms that prioritize academic achievement over physical activity. To address sedentary lifestyles among children, there is a need for a comprehensive approach that addresses both the individual and societal factors contributing to the problem. This might include increasing access to healthy food options, promoting physical activity, and implementing education programs to raise awareness about the importance of healthy eating and physical activity, as well as limiting screen time.